How patients perceive the role of hospital chaplains: a preliminary exploration. Issue 3 (September 1995) - Ellis, J M; McManus, C; Newton, B A
Abstract : OBJECTIVE--An exploratory study of the attitudes of hospital patients to the service provided by hospital chaplains. DESIGN--Questionnaire study of hospital inpatients in December 1992. SETTING--One large teaching hospital in London. PATIENTS--180 hospital inpatients in 14 different general wards, 168 (93%) of whom agreed to take part. MAIN MEASURES--Attitudes to chaplains and their role contained in 12 questions developed during a pilot study on hospital inpatients (16) and staff (14) and their relation to patients' age, sex, length of hospital stay, and religious beliefs, according to Kendall rank order correlations. RESULTS--Of 168(93%) respondents, 72(43%) were women; mean age of patients was 63.1 (SD 16.8) years. Forty five (27%) were inpatients of three days or less and 22(13%) for one month or more. 136(81%) were Christian; 17(10%) atheist, agnostic, or had no religion; and 15(9%) were of other religions. In general, patients showed positive attitudes towards the role of hospital chaplains and to the services they provided. The correlation analysis showed that there was a significant tendency for older patients, those who had been inpatients for longer, and those with religious beliefs to be more sympathetic to the role of hospital chaplains. CONCLUSIONS--Hospital chaplains provide a service which is appreciated by patients. This study provides a simple instrument for assessing patients' attitudes to chaplains.